Antibacterial activity of a novel antimicrobial peptide [W7]KR12-KAEK derived from KR-12 against Streptococcus mutans planktonic cells and biofilms - da Silva, B. R.; Conrado, A. J.S.; Pereira, A. L.; Evaristo, F. F.V.; Arruda, F. V.S.; Vasconcelos, M. A.; Lorenzón, E. N.; Cilli, E. M. [UNESP]; Teixeira, E. H. (Taylor & Francis, 2017)
The aims of this study were to describe the synthesis of a novel synthetic peptide based on the primary structure of the KR-12 peptide and to evaluate its antimicrobial and anti-biofilm activities against Streptococcus mutans. The antimicrobial effect of KR-12 and [W7]KR12-KAEK was assessed by determining the minimum inhibitory (MIC) and minimum bactericidal (MBC) concentrations. The evaluation of anti-biofilm activity was assessed through total biomass quantification, colony forming unit counting and scanning electron microscopy. [W7]KR12-KAEK showed MIC and MBC values ranging from 31.25 to 7.8 and 62.5 to 15.6 μg ml−1, respectively. Furthermore, [W7]KR12-KAEK significantly reduced biofilm biomass (50–100%). Regarding cell viability, [W7]KR12-KAEK showed reductions in the number of CFUs at concentrations ranging from 62.5 to 7.8 μg ml−1 and 500 to 62.5 μg ml−1 with respect to biofilm formation and preformed biofilms, respectively. SEM micrographs of S. mutans treated with [W7]KR12-KAEK suggested damage to the bacterial surface. [W7]KR12-KAEK is demonstrated to be an antimicrobial agent to control microbial biofilms.
Keywords: Antimicrobial peptide; biofilm; dental caries; Streptococcus mutans